Structural stratification of Sr1 − xCaxRuO3 thin films: Influence of aging process. Issue 2 (25th October 2012) - Młynarczyk, Marcin; Szot, Krzysztof; Poppe, Ulrich; Breuer, Uwe; Mi, Shaobo; Psiuk, Bronisław; Görlich, Edward A.; Tomala, Krzysztof; Waser, Rainer
Abstract Epitaxial Sr1 − xCaxRuO3 thin films were grown on SrTiO3 and LaAlO3 substrates with use of high pressure dc‐sputtering. A number of complementary methods: X‐ray diffraction (XRD), Rutherford backscattering (RBS), high resolution transmission electron microscopy (HRTEM), time‐of‐flight secondary ion mass spectrometry (ToF‐SIMS), atomic force microscopy (AFM), and X‐ray photoemission spectroscopy (XPS) was used to characterize both in‐depth and lateral structure features. Fully strained thin films were obtained with a tetragonal lattice cell pronouncedly elongated in an out‐of‐plane direction, independent on details of deposition conditions. Growth types varied from a single layer‐by‐layer two‐dimensional (2D) mode to three‐dimensional (3D) spiral precipitations of different size. Interface layer between the substrate and the thin film as well as its surface suffer from considerable deviations from nominal stoichiometry, basically resulting from Ru deficiency. Samples stored under normal conditions undergo further compositional change of the surface region. The process of aging, extended over several days, involves incorporation of water and carbon dioxide present in an ambient atmosphere and a subsequent surface reconstruction. For samples deposited on SrTiO3 the valence band is indicative of a metallic character of the sample interior regardless of Ca content. The heterogeneous in‐depth profile of the thin films is extremely important in fabrication of nanodevices, especially those based on ultrathin layers. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> Examination summary of Sr0.8Ca0.2RuO3 thin films, deposited on SrTiO3, methods used and essential conclusions.